2011
DOI: 10.1007/s00784-011-0535-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical periodontal therapy with and without subgingival minocycline administration in patients with poorly controlled type II diabetes: a randomized controlled clinical trial

Abstract: The aim of this study was to evaluate changes in clinical parameters and levels of inflammatory biomarkers in plasma in periodontal patients with poorly controlled type 2 diabetes mellitus (T2DM) after non-surgical periodontal therapy. Twenty-eight poorly controlled T2DM patients were randomly assigned to treatment with scaling and root planning (SRP) and SRP + subgingival minocycline administration. Clinical parameters, including the probing depth (PD), bleeding on probing (BOP), plaque score (PS), clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 51 publications
4
41
0
3
Order By: Relevance
“…Among studies with an active comparator, only 3 of 6 trials compare periodontal therapy+antibiotics to periodontal therapy alone[50,51,56] and these results show no evidence that antibiotic therapy provides stronger reductions in CRP. However, there is considerable heterogeneity between study.…”
Section: Resultsmentioning
confidence: 99%
“…Among studies with an active comparator, only 3 of 6 trials compare periodontal therapy+antibiotics to periodontal therapy alone[50,51,56] and these results show no evidence that antibiotic therapy provides stronger reductions in CRP. However, there is considerable heterogeneity between study.…”
Section: Resultsmentioning
confidence: 99%
“…Non‐surgical periodontal therapy (NSPT) (with and without adjunctive remedies) is a classic non‐surgical therapy for treating periodontitis 6,10,19,20 . It was reported that NSPT is effective in reducing the levels of proinflammatory cytokines in GCF from patients with periodontitis with and without type 2 diabetes 10 .…”
mentioning
confidence: 99%
“…These literatures included nine literatures that were not RCTs [15][16][17][18][19][20][21][22][23] , six in which the method of periodontal treatment was not SRP 13,[24][25][26][27][28] , two in which the participants were not patients with type 2 diabetes and periodontal disease 29,30) , one in which the outcome variable was not HbA1c 31) , and two without data 32,33) .…”
Section: Discussionmentioning
confidence: 99%